1997
DOI: 10.1046/j.1365-201x.1997.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional difference in lipolysis caused by a β‐adrenergic agonist as determined by the microdialysis technique

Abstract: We have investigated the difference in lipolysis caused by a beta-adrenergic agent between visceral and abdominal subcutaneous adipose tissues in vivo. Glycerol levels (lipolysis index) were continuously monitored in mesenteric and abdominal subcutaneous adipose tissues of anaesthetized Wistar rats using the microdialysis technique. During microdialysis, increasing concentrations of the lipolytic agent, isoproterenol (10(-8), 10(-7), 10(-6), 10(-5) mol L-1), were added to the perfusion. Glycerol concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…At tbe end of food deprivation on December 21 between 1200 and 1400 hours, the birds were anesthetized with intramuscular ketamine and xylazine and euthanized with intracardial embutramide, mebezonium iodide, and tetracaine bydrochloride. Samples were taken from the liver and from the IAB (mesenteric) and SC (flank) fat tissues because the rates of lipolysis differed between these adipose tissue sites in mammals (Iwao et al 1997). All samples were frozen in liquid nitrogen and stored at -80"C.…”
Section: Methodsmentioning
confidence: 99%
“…At tbe end of food deprivation on December 21 between 1200 and 1400 hours, the birds were anesthetized with intramuscular ketamine and xylazine and euthanized with intracardial embutramide, mebezonium iodide, and tetracaine bydrochloride. Samples were taken from the liver and from the IAB (mesenteric) and SC (flank) fat tissues because the rates of lipolysis differed between these adipose tissue sites in mammals (Iwao et al 1997). All samples were frozen in liquid nitrogen and stored at -80"C.…”
Section: Methodsmentioning
confidence: 99%
“…No data on SGA subjects isoproterenol concentrations, while basal lipolysis was identical in the two depots [94]. Omental fat has been reported to be relatively resistant to insulin suppression of lipolysis in vitro and sensitive to β3-adrenergic stimulation of lipolysis [95].…”
Section: Fat Partitioning and Lipolysismentioning
confidence: 99%
“…[2][3][4][5] These metabolic abnormalities are associated with the characteristics of visceral adipocytes. Previous in vitro studies in humans [6][7][8][9][10] have provided data that lipolytic responses to catecholamines of visceral adipocytes are 1.5-3.0 times higher than subcutaneous ones. Furthermore, it has been reported that visceral adipocytes have a lower antilipolytic response to insulin 7,11 than subcutaneous adipocytes.…”
Section: Introductionmentioning
confidence: 99%